Makna dan Nilai Opo Mpole Ka Lima Mpulu Ngkau pada Upacara Perkawinan Adat Kulawi (Kajian Hermeneutika) - Yunidar, Yunidar; Harisa, Sitti; Ferdinand, Frans (Jurnal Kreatif Online, 2020)
This study aimed to examine the meaning, value and function of the â€œopo mpole ka lima mpulu ngkauâ€ at the Kulawi traditional ceremony in the study of hermeneutics. This research was a qualitative study using an interactive data analysis model. The data were collected using open interview techniques in depth. Based on the results of the research obtained, it can be concluded that in the traditional language